3D contour fluorescence spectroscopy with Brus model: Determination of size and band gap of double stranded DNA templated silver nanoclusters. (January 2018) - Kamalraj, Devaraj; Yuvaraj, Selvaraj; Yoganand, Coimbatore Paramasivam; Jaffer, Syed S.
Abstract: Here, we propose a new synthetic methodology for silver nanocluster preparation by using a double stranded-DNA (ds-DNA) template which no one has reported yet. A new calculative method was formulated to determine the size of the nanocluster and their band gaps by using steady state 3D contour fluorescence technique with Brus model. Generally, the structure and size of the nanoclusters determine by using High Resolution Transmission Electron Microscopy (HR-TEM). Before imaging the samples by using HR-TEM, they are introduced to drying process which causes aggregation and forms bigger polycrystalline particles. It takes long time duration and expensive methodology. In this current methodology, we found out the size and band gap of the nanocluster in the liquid form without any polycrystalline aggregation for which 3D contour fluorescence technique was used as an alternative approach to the HR-TEM method. Graphical abstract: Image 1 Graphic representation of the formation of different emissive colour from blue to red in ds-DNA-AgNC with respect to amount silver. Highlights: We reported a novel method for the preparation of AgNCs on ds-DNA template (no sequence specificity) with emission colour tunability from blue to red region which depends on the concentration of silver ions. From this method, we can synthesize different size and colour of AgNCs that could be applied to various fields from material research to bio-imaging. In this study new calculative methods to find out the size and energy band gap of AgNCs were formulated by using Brus model and 3D-contour fluorescence spectroscopy. Light radiation emission was depends on the size of AgNCs. So that different in the size of AgNCs could be applied in the different parts of the cell for biological cell imaging which could give different colour variations during the cell imaging.